(3JGQjN GdJMdjd GdfaSjs (3h eMGVQGJ aj GdJMdjd GdfaSjs - (3aQhjO, SjLehfOs 1856 - 1939; (3GdUHGZ, GMeOs; (3GdedG, LjfGs; (3LeGd, ESdGes; (3ShGM, SGde YHO GdeYRs ((3GdefhajI, eUQs (3OGQ MhGOjJ ddfTQ hGdJhRjYs, 2022)
(3dG jMJGL CMO Edi Cf ojaGLC HGdWGHY GdPGJj ddeSGgeI GdJj CbJQM JbOjegG gfG dJGQjN MQcI GdJMdjd GdfaSj, hdG jMJGL Cj TNU Edi GdJSGDd Yf GdOhQ GdPj CdYHg ajgG, dCnqf GdJMdjd GdfaSj Yed EHOGYj, deOI YTQ SfhGJ cfoJ GdTNU GdhMjO GdPj jgJe HgG, hcd GdGSJjGA GdPj CKGQJg GdXGgQI GdLOjOI aj eYGUQj cGf jJOab aj Tcd GfJbGOGJ Ydi QCSj, Ydi GdQZe ef Cfg eVi hbJ Whjd efP Cf cfoJ GdoeMdd GdfaSj GdhMjO, EdG Cffj CYJHQ faSj oeHQkQG ddEHbGA Ydi Cfg MJi Gdjhe dG jecf dCMO Cf jYQa Cnqf CaVd eG CaYdg gh GdJMdjd GdfaSj, hcja jNJda Yf GdWQb GdCNQi ddJMbjb aj MjGI GdYbd, hYdi hLg GdJMOjO eG jLH JSejJg HGdJMdjd GdfaSj heG ojecf hUag HTcd CaVd HGSe BNQ, aj gPG GdJfUd enqeG jHOh dj YekdG QGFkYG ef CYeGd GdGZJUGH, aCfG CHdZ obnqQGA gPG GdcJGH GdSfhj HTcd ZjQ oeHGTQ HGdCMOGK GdJj COJ Edi GdJZjjQGJ aj JMQjQg hUjZJgs
Keywords: (3Yde GdfaSs -- (3JGQjNs